2016
DOI: 10.3892/mmr.2016.4779
|View full text |Cite|
|
Sign up to set email alerts
|

Upregulation of microRNA-27b contributes to the migration and invasion of gastric cancer cells via the inhibition of sprouty2-mediated ERK signaling

Abstract: MicroRNAs (miRs) have been demonstrated to be associated with the development, progression and prognosis of gastric cancer. However, the exact role of miR‑27b in the regulation of gastric cancer cells and the underlying mechanisms remain unclear. In the current study, it was demonstrated that miR‑27b was significantly upregulated in gastric cancer tissues and cell lines, compared with their matched normal adjacent tissues and normal gastric epithelial cells, respectively. Luciferase reporter assay data indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This data indicated that miR-23a was able to activate the ERK signaling via the inhibition of SPRY2, and thus promote the malignant phenotypes of AGS cells. Similarly, a previous study also indicated that miR-27a was able to promote the migration and invasion of gastric cancer cells via inhibiting the expression of SPRY2, and thus activating ERK signaling ( 32 ).…”
Section: Discussionmentioning
confidence: 69%
“…This data indicated that miR-23a was able to activate the ERK signaling via the inhibition of SPRY2, and thus promote the malignant phenotypes of AGS cells. Similarly, a previous study also indicated that miR-27a was able to promote the migration and invasion of gastric cancer cells via inhibiting the expression of SPRY2, and thus activating ERK signaling ( 32 ).…”
Section: Discussionmentioning
confidence: 69%
“…Mechanistically, miR-1323 promoted the migration of lung cancer cells by targeting Cbl-b. It is well-known that microRNAs are involved in multiple biological processes such as cell differentiation, proliferation, apoptosis, EMT, and cell migration, through targeting gene expression (21)(22)(23). Previously, a study has shown that miR-1323 promoted radiation-resistant lung cancer cells (10).…”
Section: Discussionmentioning
confidence: 99%
“…Except for regulating EMT, miRNA-27b plays a vital role in the transfer via inhibiting multiple genes that are associated with motility and migration at the post-transcriptional level. SPRY2-mediated ERK signaling activation may be another mechanism for miR-27b inducing the invasion and of migration of GC cells proved by Jiang et al 57 MiR-27b is decreased in metastatic, castration-resistant PCa tissue and cells, and suppresses migration and invasion which are key metastatic processes in PCa cells ALVA31 and PC3-ML. These inhibitory effects on migration and invasion are concomitant with decreased activity of Rac1 without affecting total Rac1 levels and enhanced level of tumor suppressor E-cadherin.…”
Section: Introductionmentioning
confidence: 94%